Incidence of intracranial injury in orbital wall fracture patients not classified as traumatic brain injury. Issue 5 (May 2018) - Lee, Hyung-Joo; Kim, Youn-Jung; Seo, Dong-Woo; Sohn, Chang Hwan; Ryoo, Seung Mok; Ahn, Shin; Lee, Yoon-Seon; Kim, Won Young; Lim, Kyoung Soo
Abstract: Objective: The detection of intracranial injury in patients with facial injury rather than traumatic brain injury (TBI) remains a challenge for emergency physicians. This study aimed to evaluate the incidence and risk factors of intracranial injury in patients with orbital wall fracture (OWF), who were classified with a chief complaint of facial injury rather than TBI. Methods: This retrospective case-control study enrolled adult OWF patients (age ≥18 years) who presented at the hospital between January 2004 and March 2016. Patients with definite TBI were excluded because non-contrast head computed tomography (CT) is recommended for such patients. Results: A total of 1220 patients with OWF were finally enrolled. CT of the head was performed on 677 patients, and the incidence of concomitant intracranial injury was found to be 9% (62/677). Patients with definite TBI were excluded. Symptoms raising a suspicion of TBI, such as loss of consciousness, alcohol intoxication, or vomiting, were present in 347 of the patients, with 44 of these patients (13%) showing a concomitant intracranial injury. Of the 330 patients without such symptoms, 18 (6%) demonstrated a concomitant intracranial injury. In OWF patients, superior wall fracture (odds ratio [OR], 4.15; 95% confidence interval [CI], 2.06–8.34; P <  0.001), associated frontal bone fracture (OR, 4.38; 95% CI, 2.08–9.23; P  < 0.001), and older age (decades) (OR, 1.03; 95% CI, 1.01–1.04; P  = 0.002) were independent risk factors for concomitant intracranial injury. Conclusions: Emergency physicians should maintain a high degree of suspicion of TBI, even when their primary concern is facial trauma with OWF. Head CT is recommended for OWF patients with a superior OWF, frontal bone fracture, or increased age.